2015
DOI: 10.1080/03721426.2015.1074341
|View full text |Cite
|
Sign up to set email alerts
|

Scatting behaviour of the sleepy lizard,Tiliqua rugosa

Abstract: The use of chemical signals for communication is wide spread in many animal taxa.Squamates in particular have a highly developed vomeronasal system and investigate chemical signals through tongue flicking. In some lizard species, individuals have been shown to be able use chemical signals, including those from faeces (scats), for discriminating between kin and conspecifics and members and non-members of social groups. The Australia scincid lineage Egernia, is one group that has an unusually high number of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For enteric bacteria with a fecal-oral transmission pathway among individual hosts, the pattern of fecal deposition by the host is an important ecological consideration. Sleepy lizards appear to scat haphazardly as they move around their home ranges (21). Our aim was to describe any spatial patterning and subspecies diversity of S. enterica within individual sleepy lizards and to determine whether any spatial patterns were driven primarily by the environment outside the host or by competition among subspecies within the host.…”
mentioning
confidence: 99%
“…For enteric bacteria with a fecal-oral transmission pathway among individual hosts, the pattern of fecal deposition by the host is an important ecological consideration. Sleepy lizards appear to scat haphazardly as they move around their home ranges (21). Our aim was to describe any spatial patterning and subspecies diversity of S. enterica within individual sleepy lizards and to determine whether any spatial patterns were driven primarily by the environment outside the host or by competition among subspecies within the host.…”
mentioning
confidence: 99%
“…Unlike other species in the sub‐family Egerniinae, sleepy lizards do not make use of scat piling to indicate occupancy of their home ranges, but rather likely employ other forms of scent marking (Fenner et al . ; Leu et al . ).…”
Section: Distribution and Habitatmentioning
confidence: 99%
“…Despite this, few studies to date have focused on space use and refuge choice. Fenner et al () found that rather than scat‐piling, Tiliqua rugosa (sleepy lizard) scat haphazardly within their home range. In contrast, Tiliqua adelaidensis (pygmy bluetongue) consistently scat in a direction aligned with the refuge of the nearest neighbour (Fenner & Bull ).…”
Section: Introductionmentioning
confidence: 99%